2010
DOI: 10.1007/s10533-010-9440-7
|View full text |Cite
|
Sign up to set email alerts
|

Release of CO2 and CH4 from lakes and drainage ditches in temperate wetlands

Abstract: Shallow fresh water bodies in peat areas are important contributors to greenhouse gas fluxes to the atmosphere. In this study we determined the magnitude of CH 4 and CO 2 fluxes from 12 water bodies in Dutch wetlands during the summer season and studied the factors that might regulate emissions of CH 4 and CO 2 from these lakes and ditches. The lakes and ditches acted as CO 2 and CH 4 sources of emissions to the atmosphere; the fluxes from the ditches were significantly larger than the fluxes from the lakes. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
101
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(120 citation statements)
references
References 48 publications
16
101
2
1
Order By: Relevance
“…The importance of small open water bodies in wetlands as considerable GHG sources was highlighted in previous studies (e.g. by Schrier-Uijl et al, 2011;Zhu et al, 2012;IPCC, 2014) and in the case of CH 4 even for landscape-scale budgets (e.g. by Repo et al, 2007).…”
mentioning
confidence: 87%
“…The importance of small open water bodies in wetlands as considerable GHG sources was highlighted in previous studies (e.g. by Schrier-Uijl et al, 2011;Zhu et al, 2012;IPCC, 2014) and in the case of CH 4 even for landscape-scale budgets (e.g. by Repo et al, 2007).…”
mentioning
confidence: 87%
“…Emission rates in a temperate climate ranged from 12.7 to 27.3 tCO 2 eqha -1 yr -1 (Table 4), thus an average emission rate of 20 tCO 2 eqha -1 yr -1 was assumed for the ditches and ponds at Pollboy for the 120-year life cycle. [49] Mesotropic/eurotrophic status 27.3 Schrier-Uijl et al [47] Eutrophic fen (intensive) 25.4 Schrier-Uijl et al [47] Eutrophic fen (less intensive) 12.3 Hendriks et al [46] Restored agricultural peat meadow 12.7 Average 19.4 (~20) Figure 6 -Clogged stream diversion shown at front and peat disposal area in background at Pollboy 3 years after construction…”
Section: Drainage Systemsmentioning
confidence: 99%
“…Lake sediments produce large quantities of greenhouse gases (GHGs), including carbon dioxide (CO 2 ), methane (CH 4 ), and nitrous oxide (N 2 O), through biological processes (Bastviken et al 2004;Schrier-Uijl et al 2011). Previous studies have shown that, globally, lakes have emitted 71.6 Tg CH 4 /yr and 1943 Tg CO 2 /yr into the atmosphere (Tranvik et al 2009;Bastviken et al 2010Bastviken et al , 2011.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is reported that GHG emissions from global lakes are still underestimated and poorly constrained due to the spatial variation of GHG emissions and an impoverished understanding of the mechanisms behind GHG production (Yang et al 2011;IPCC 2013). Especially, past studies about GHG emissions in lake ecosystems have mainly focused on the sources and sinks of GHGs or the relationships between GHG effluxes and various abiotic factors (Bastviken et al 2011;Schrier-Uijl et al 2011;Liu et al 2013). In fact, abiotic factors influence GHG effluxes by affecting microbes which degrade organic matter to produce GHGs in lake sediments.…”
Section: Introductionmentioning
confidence: 99%